2011
DOI: 10.1007/s00271-011-0279-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil water content on drip irrigated cotton: comparison of measured and simulated values obtained with the Hydrus 2-D model

Abstract: Crop irrigation with subsurface drip (SDI) is increasing in the semiarid Texas High Plains (THP). Information on drip-tubing positioning, irrigation strategies, and wetted soil area is needed to increase rainwater effectiveness when well capacities are inadequate to meet full irrigation requirements. Time and resources necessary to test SDI strategies for different conditions through field experimentation is too large. However, a mechanistic model such as Hydrus-2D can quantify the effect of different installa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 35 publications
(38 reference statements)
1
27
0
Order By: Relevance
“…Overall, the changes in the simulated SWCs at 0-30 cm were more drastic than those at 30-90 cm in both irrigation treatments (Figures 11 and 12), since the 0-30 cm layer is more directly affected by irrigation, precipitation, evaporation, and transpiration [21,24]. The simulation results in Figures 11 and 12 showed that the HYDRUS-2D model overestimated the SWCs in July 2013.…”
Section: Modeling Soil Water Movement Under Different Irrigation Methodsmentioning
confidence: 62%
See 4 more Smart Citations
“…Overall, the changes in the simulated SWCs at 0-30 cm were more drastic than those at 30-90 cm in both irrigation treatments (Figures 11 and 12), since the 0-30 cm layer is more directly affected by irrigation, precipitation, evaporation, and transpiration [21,24]. The simulation results in Figures 11 and 12 showed that the HYDRUS-2D model overestimated the SWCs in July 2013.…”
Section: Modeling Soil Water Movement Under Different Irrigation Methodsmentioning
confidence: 62%
“…The HYDRUS-2D model and the dual crop coefficient approach of FAO-56 were calibrated using the measured data in 2014, and produced a cumulative bias under the extreme rainfall conditions in 2013. Nevertheless, the simulated and measured results in 2013 still exhibited highly consistent trends, with several consecutive irrigation and precipitation events in the transplanted cotton growing seasons, particularly considering the complexity of the conditions to which the model was applied (i.e., heterogeneous soil properties, a more than 120-day simulation period, high evaporative demand, and assumed constant root distribution in one growth stage) [21,24].…”
Section: Modeling Soil Water Movement Under Different Irrigation Methodsmentioning
confidence: 99%
See 3 more Smart Citations